Koperasi siswa UiTM Selangor Berhad case study / Raudhah 'Aqilah Rahimie, Muhammad Hazwan Ab Hamid and Suriana Abdullah - RAHIMIE, RAUDHAH'AQILAH; AB HAMID, MUHAMMAD HAZWAN; ABDULLAH, SURIANA (2018)
This case study was commissioned to examine problem that contains a real orhypothetical situation that also includes the complexities of KoSiswa would encounter in the convenience store business over the past six years since in 2011 to 2017.The finding draws attention to the fact that problems in Siswa Save, Kolej Melati, UiTM Shah Alam shows some major and minor problems. Firstly, the majorproblems KoSiswa faced are the prices offered that is higher compared to the other convenience stores' average pricing. Besides, KoSiswa also lack of product variety in the convenience store. The store usually only meets the needs of the users who live in close proximity. Further observation reveal that this market shrinkage coincided with an increase in basic needs among consumers or student who regard the variety product or services supply from nearby convenience store. Moreover, KoSiswa has poor marketing strategy.They do not really active in the way they advertise and promote their brand and services. In conclusion, this case study will be evaluating this range and concludes that it would be an ideal candidate to meet the challenge presented by the market and could satisfy the new consumer demand.